CTNNAL1 participates in the regulation of mucus overproduction in HDM‐induced asthma mouse model through the YAP‐ROCK2 pathway. Issue 5 (28th January 2022) - Wu, Di; Jiang, Wang; Liu, Caixia; Liu, Lexin; Li, Furong; Ma, Xiaodi; Pan, Lang; Liu, Chi; Qu, Xiangping; Liu, Huijun; Qin, Xiaoqun; Xiang, Yang
Abstract: Our previous study indicated that adhesion molecule catenin alpha‐like 1(CTNNAL1) is downregulated in airway epithelial cells of asthma patients and asthma animal model but little is known about how the CTNNAL1 affects asthma pathogenesis. To reveal the direct relationship between asthma and CTNNAL1, CTNNAL1‐deficient mouse model in bronchopulmonary tissue was constructed by introducing CTNNAL1‐siRNA sequence using adeno‐associated virus (AAV) as vector. The mouse model of asthma was established by stimulation of house dust mite (HDM). After HDM‐challenged, there was marked airway inflammation, especially mucus hypersecretion in the CTNNAL1‐deficient mice. In addition, the CTNNAL1‐deficient mice exhibited an increase of lung IL‐4 and IL‐13 levels, as well as a significant increase of goblet cell hyperplasia and MUC5AC after HDM exposure. The expression of Yes‐associated protein (YAP), protein that interacted with α‐catenin, was downregulated after CTNNAL1 silencing and was upregulated due to its overexpression. In addition, the interaction between CTNNAL1 and YAP was confirmed by CO‐IP. Besides, inhibition of YAP could decrease the secretion of MUC5AC, IL‐4 and IL‐13 in CTNNAL1‐deficient 16HBE14o‐cells. Above results indicated us that CTNNAL1 regulated mucus hypersecretion through YAP pathway. In addition, the expression of ROCK2 increased when CTNNAL1 was silenced and decreased after YAP silencing, and inhibition of YAP decreased the expression of ROCK2 in CTNNAL1‐deficient HBE cells. Inhibition of ROCK2 decreased MUC5AC expression and IL‐13 secretion. In all, our study demonstrates that CTNNAL1 plays an important role in HDM‐induced asthma, mediating mucus secretion through the YAP‐ROCK2 pathway.